Study of the Effect of Tramadol on Sperm Standards in Male White Rats - Marwah Ahmed Miri (Journal of Global Pharma Technology, 2019)
Tramadol is an opioid analgesic, a pain reliever used by the World Health Organization (WHO) to treat postoperative pain and chronic diseases such as acute liver disease, Fibromyalgia and Arthritis. This study was designed to determine the effect of tramadol in fertility in male white rats. White rats were used as an example of mammalian animals. The study included the use of 45 white adults. Animals were raised in the Animal House of the Faculty of Education for Girls / University of Kufa under standard conditions in terms of temperature, light and nutrition.  The study was conducted to assess the damage to the male reproductive tract of white rats due to daily exposure to tramadol. The groups was given orally distilled water as a control group and the other groups were given two doses of tramadol (100, 200 mg) Kg / kg) orally for 8 weeks. The results in this study showed a significant decrease (P <0.05) in body weight, testosterone, albino, seminal vesicles and prostate glands in the treated groups (100, 200 mg / kg) of tramadol compared to control group. The results of the statistical analysis in the present study showed a significant decrease (P <0.05) in the concentration of sperm in the testis and the epididymal tail and a significant decrease (P <0.05) in the percentage of sperm movement in the testis and epididymis, (P <0.05) in the percentage of non-mutated sperm in the serum groups (100, 200 mg / kg) of tramadol compared to the control group.Keywords: Tramadol, Sperm.